2013
DOI: 10.1099/vir.0.045682-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CD8+ T-cell recognition in the immediate-early phase of human cytomegalovirus infection

Abstract: Human cytomegalovirus (HCMV) interferes with MHC class I-restricted antigen presentation and thereby reduces recognition by CD8 + T-cells. This interference is mediated primarily by endoplasmic reticulum-resident glycoproteins that are encoded in the US2-11 region of the viral genome. Such a suppression of recognition would be of particular importance immediately after infection, because several immunodominant viral antigens are already present in the cell in this phase. However, which of the evasion proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…We want to point out that both mutants also lacked ORFs US2 to US6 encoding immune evasins and were therefore expected to modulate HLA expression to a lesser extent than wildtype CMV (61). This characteristic of the mutants appeared to be a prerequisite for measuring the influence of UL11 on T cell activity, because many CMV-specific T cells are hardly activated when HLA levels are diminished (62,63). Immunoblot analysis of cells infected with the two mutants confirmed the similar expression of the IE1 and pp65 proteins (Fig.…”
Section: Expression Of Ul11 Proteins During the Lytic CMV Infection Cmentioning
confidence: 99%
“…We want to point out that both mutants also lacked ORFs US2 to US6 encoding immune evasins and were therefore expected to modulate HLA expression to a lesser extent than wildtype CMV (61). This characteristic of the mutants appeared to be a prerequisite for measuring the influence of UL11 on T cell activity, because many CMV-specific T cells are hardly activated when HLA levels are diminished (62,63). Immunoblot analysis of cells infected with the two mutants confirmed the similar expression of the IE1 and pp65 proteins (Fig.…”
Section: Expression Of Ul11 Proteins During the Lytic CMV Infection Cmentioning
confidence: 99%
“…Viral mutants that expressed US2-11 but comparable levels of pp71 showed markedly reduced levels of IE1 presentation under IE conditions. This indicated that at least one of these immunoevasins was operative at IE times (27). However, the increase in IE1 presentation by pp71 overexpression could not be overcome by US2-11, although presentation remained at a lower level, compared to US2-11-negative viruses.…”
Section: Discussionmentioning
confidence: 83%
“…Cells infected with the wt strain AD169 (RV-HB15) showed only very limited IE1 presentation. We recently showed that gpUS2 and gpUS11 were expressed and effective under these IE conditions (27), but again, enhanced levels of pp71 in cells infected with AD169/EYFP-pp71_⌬US2-11 also correlated with roughly 3-fold more spots in the absence of US2-11. This suggested that gpUS2-11 had no limiting effect on the relative enhancement of IE gene expression through particleassociated pp71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of these proteins prevents peptide transport [49], retains MHC class I molecules in the ER [49], and targets MHC class I molecules for degradation [50]. A recent publication noted that of the US2-11 family, specific expression of the HCMV proteins gpUS2 and gpUS11 were both required to reduce MHC class I expression on infected cells and inhibition of CD8 T-cell-mediated killing of virally infected cells [51]. However, not all MHC haplotypes are equally inhibited by these viral evasion proteins [52].…”
Section: Cd8 T Cell Responsementioning
confidence: 99%